Local muscle oxygenation during different cuff-pressures intervention: a punctual near-infrared spectroscopy measurement - Anderson Meireles; Géssyca T. de Oliveira; Hiago L. R. de Souza; Rhaí A. Arriel; Luis Leitão; Marcelo P. dos Santos; Moacir Marocolo (Universidade Estadual Paulista (UNESP), 2022)
Abstract Aim: To verify the response of tissue saturation index (TSI) during ischemia-reperfusion (IR) interventions with different cuff-pressures. Methods: Twenty-nine healthy men experienced in resistance training were recruited. Each one has undergone a control condition (no cuff) and one of the three IR interventions: 1) 190 mmHg (CP-190, 22.7 ± 3.0 years; 176.6 ± 3.9 cm; 77.3 ± 9.5 kg; 2) 100 mmHg (CP-100, 22.9 ± 6.3 years; 180.5 ± 4.0 cm; 85.2 ± 14.1 kg) and 3) 20 mmHg (CP-20, 20.3 ± 2.4 years; 171.8 ± 5.2 cm; 72.4 ± 6.0 kg). Cuffs were placed on the proximal region of the thighs. IR interventions consisted of three cycles of 2-min occlusion-reperfusion. TSI was measured using near-infrared spectroscopy (NIRS), positioned on the middle portion of the vastus lateralis of the dominant leg. The oxygenation was measured at the control conditions (no cuff) and during cuff interventions. Results: While TSI values of CP-20 did not change compared to control (p > 0.05), the TSI in CP-190 was lower in the ischemia (p < 0.05), and CP-100 was lower in the second and third ischemia (p < 0.05). However, the TSI value increased during reperfusion but did not return to control levels (p < 0.05). Conclusion: TSI of the CP-190 significantly decreased during ischemia. However, these values increased by about 16% in the reperfusion period. Thus, our results show that the RI intervention may have caused an increase in metabolic demand, as even with the release of blood flow, the TSI values were below those of the other interventions.